Air cargo: the neglected area - Echevarne, Rafael (Henry Stewart Talks, 2009)
Characteristics of the air cargo industry, Cargo Airport profiles, Key issues in air cargo, Trends in air cargo, Drivers and constraints of air cargo, Impact of air cargo on airport revenues, Marketing homework for cargo airports, Factors influencing airport selection, Classic air cargo marketing flaws, Air cargo development strategies